2009
DOI: 10.1016/j.ultsonch.2008.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous extraction of phenolic compounds of citrus peel extracts: Effect of ultrasound

Abstract: Ultrasound-assisted extraction (UAE) has been widely applied in the extraction of a variety of biologically active compounds including phenolic compounds. However, there is an insufficiency of information on simultaneous extraction of these compounds in this area. In the present study, seven phenolic compounds of two families including cinnamic acids (caffeic, p-coumaric, ferulic, sinapic acid), and benzoic acids (protocatechuic, p-hydroxybenzoic, vanillic acid) from citrus (Citrus unshiuMarc) peels were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
114
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(134 citation statements)
references
References 29 publications
15
114
1
4
Order By: Relevance
“…In general, concentrations of phenolic compounds were slightly lower in microwave extraction as compared to conventional extraction (Table 2). Ma et al (2009) also showed that microwave radiation can easily degrade unstable phenolics due to their structural properties. Phenolic compounds with higher number of hydroxyl group in their aromatic rings are unstable and can easily be degraded under microwave radiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, concentrations of phenolic compounds were slightly lower in microwave extraction as compared to conventional extraction (Table 2). Ma et al (2009) also showed that microwave radiation can easily degrade unstable phenolics due to their structural properties. Phenolic compounds with higher number of hydroxyl group in their aromatic rings are unstable and can easily be degraded under microwave radiation.…”
Section: Resultsmentioning
confidence: 99%
“…1c). Increasing power level of ultrasound supplies a faster and stronger mixing effect that reduces external resistance and enhances the mass transfer, so increasing power enhances the extraction and increases the efficiency (Chemat et al 2004;Ma et al 2009;Shalmashi 2009). By means of ultrasound, mixing occurs in the solid-liquid interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RA enrichment In the present work, an economically feasible, low timeconsuming, safe, and efficient method has been proposed for the isolation, extraction, and purification of biosynthetic production of RA by T. pseudopulegioides. The wild species and micropropagated plantlets were assessed for RA production employing a traditional water extraction process involving acidification and then extraction with ethyl acetate (Ma et al, 2009). HPLC results revealed that among the all samples the highest RA was found in KINsupplied medium, among which KIN-2 produced the highest RA.…”
Section: Phenolic Profilesmentioning
confidence: 99%
“…The extraction of bioactive compounds under ultrasound irradiation at frequency of 20-100 kHz is one of the newest extraction techniques that may offer high reproducibility in shorter times, simplified manipulation, reduced solvent consumption and temperature and lower energy input (Chemat et al 2008). Optimisation of ultrasound assisted extraction has been described recently to extract hesperidin from Penggan (Citrus reticulata) peel (Ma et al 2008a), phenolic acids and flavanone glycosides from Satsuma Mandarin (Citrus unshiu Marc) peel (Ma et al 2009;Ma et al 2008b) and total phenolic content from Penggan peel (Ma et al 2008a). …”
Section: Introductionmentioning
confidence: 99%